2016
DOI: 10.1142/s0217984916501554
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical study on cooling flow field designs performance of PEM fuel cell with variable heat flux

Abstract: In PEM fuel cells, during electrochemical generation of electricity more than half of the chemical energy of hydrogen is converted to heat. This heat of reactions, if not exhausted properly, would impair the performance and durability of the cell. In general, large scale PEM fuel cells are cooled by liquid water that circulates through coolant flow channels formed in bipolar plates or in dedicated cooling plates. In this paper, a numerical method has been presented to study cooling and temperature distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Since the current density in the fuel cell is not uniform, the heat flux will change along the cell. According to the reported data of Reference , this linear variation is represented by: q=25644x+6174 where x is the distance (m) in the flow direction. The geometrical parameters, the value of heat flux imposed on the cooling surface and its variations, the flow rate of coolant, etc.…”
Section: Physical Model and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the current density in the fuel cell is not uniform, the heat flux will change along the cell. According to the reported data of Reference , this linear variation is represented by: q=25644x+6174 where x is the distance (m) in the flow direction. The geometrical parameters, the value of heat flux imposed on the cooling surface and its variations, the flow rate of coolant, etc.…”
Section: Physical Model and Assumptionsmentioning
confidence: 99%
“…However, in practice, this heat flux is not constant and is a function of local current density of the fuel cell. Here, we derive the data of cell current density curve from Reference and impose a variable heat flux on the cooling plate. We investigate the effects of porosity, pore size and thickness of metal foam, as well as nanoparticles volume fraction, on the cooling system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We simulate the heat flux imposed to the cooling plate as a variable heat flux distribution, similar to the form of the heat generated in a real PEM fuel cell. The experimental data are obtained from [29]. It is found that the thermal flux changes linearly along the channel length according to the following equation:…”
Section: Governing Equationsmentioning
confidence: 99%
“…For instance, Ebrahim Afshari and his team [11] conducted a study on the coolant flow and heat transfer in the cooling plates of proton exchange membrane fuel cells. They evaluated and compared the performance of four different coolant flow fields, including simple parallel channels and serpentine channels with one and two parallel channels, based on the maximum surface temperature, uniform temperature distribution, and pressure drop.…”
Section: Introductionmentioning
confidence: 99%